Sediment resuspension and transport in the offshore subaqueous Yangtze Delta during winter storms - Tian, Min; Yang, Haifei; Zhang, Wenxiang; Xu, Kehui; Shi, Benwei; Wang, Yaping; Yang, Shilun (Frontiers in Marine Science, 2024)
Storm-induced episodic sediment redistribution in coastal systems can reshape geomorphic bodies, disrupt ecosystems, and cause economic damage. However, cold-wave-storm-induced hydrodynamic changes and residual sediment transport in large, exposed subaqueous deltas, such as the Yangtze Delta, are poorly understood because it is typically expensive and difficult to obtain systematic field data in open coast settings during storm events. We conducted a successful field survey of waves, currents, changes in water depth, and turbidity at a station (time-averaged water depth of 20 m) in the offshore subaqueous Yangtze Delta over 10 days during winter, covering two storms and two fair-weather periods. During the storm events, strong northerly winds drove southward longshore currents ( 0.2 m/s) and resulted in increased wave height and sediment resuspension, thereby leading to massive southward sediment transport. In contrast, both southward and northward transports were limited during the fair-weather periods. A better understanding of the storm-induced sediment transport can be obtained by using an approximately half-day lag in sediment transport behind wind force, given the time needed to form waves and longshore drift, the inertia of water motion, and the slow settling velocity of fine-grained sediment. Our results directly support previous findings of southward sediment transport from the Yangtze Delta during winter, which is deposited in the Zhejiang–Fujian mud belt in the inner shelf of the East China Sea. In addition, the southward sediment transport from the Yangtze Delta occurs mainly during episodic storm events, rather than during the winter monsoon, and winter storms dominate over typhoons in driving southward sediment transport from the delta. This study highlights the importance of storms, especially during winter storms, in coastal sediment redistribution, which is of particular significance when considering the projected increase in storm intensity with global warming.